WIRID VERSES TO STRENGTHEN MEMORIZATION: STUDY OF LIVING QUR’AN READING SELECTED VERSES OF SURAH AL-BAQARAH AT PONDOK PESANTREN - Fanjah, Ilfi Nur Faizatul; Ulwiyah, Robiatul; Rahmawati, Kharolina; Al Masithoh, Silvinatin; Rahman, Azibur (MUSHAF: Jurnal Tafsir Berwawasan Keindonesiaan, 2022)
Having vital memorization or memory is the dream of everyone, including those who want to memorize the Qur’an. However, the facts on the ground are that not all of these memories are directly proportional to everyone’s wishes. One way and effort to have vital memorization is wirid from the Qur’an, as practiced at the Darussalam Islamic Boarding School in Blokagung Banyuwangi, which uses the wirid surah Al-Baqarah. Based on the practices and habits of the Darussalam Islamic boarding school, this research was appointed with a focus on studying the living Qur’an. It is hoped that later an answer can be found from the formula: how does the wirid al-Qur’an (Al-Baqarah) come alive and affect the sharpness of a santri’s memorization? As a methodical step, this research uses a descriptive-qualitative method based on a phenomenon (phenomenological). The results of this study conclude that this memorizing wirid becomes a medium to get closer to Allah by using dhikr taken from pieces of the verses of the Qur'an Surah al-Baqarah has given confidence to its practitioners as a reinforcement for memorizing the Qur’an. 'an and have made the Qur’an.